Ambient density effects on initial flow breakup and droplet size distribution of hollow-cone sprays from outwardly-opening GDI injector. (1st January 2018) - Jeon, Jeeyeon; Moon, Seoksu
Highlights: Outwardly-opening injector sprays are studied under varied ambient densities. The study focuses on the initial flow breakup and local drop size distribution. Ambient density does not alter the breakup length when initial flow is turbulent. Ambient density effects on droplet size show different aspects at each location. Increase in ambient density enhances the droplet coalescence in vortex flow region. Abstract: Outwardly-opening injectors for gasoline direct-injection engines generate hollow-cone sprays which have better atomization performance than conventional hole-type nozzle sprays. The ambient density alters the initial flow breakup and the downstream vortex structure of the hollow-cone sprays which in turn rearrange the local droplet size distribution. However, the ambient density effects on those spray properties have not been thoroughly characterized in the previous studies despite their crucial effects on engine combustion. The current study investigates the ambient density effects on the initial liquid-sheet breakup and local droplet size distribution of hollow-cone sprays from an outwardly-opening gasoline-direct-injection injector using X-ray and visible light imaging techniques. The ambient density effects were investigated in varied needle lift conditions which altered the initial flow conditions such as liquid-sheet thickness and turbulence. In general, an increase in the ambient density decreased the breakup length of the liquid-sheet but the effects became insignificant as the initial flow turbulence increased in high needle lift conditions. The spray droplet size in the near-nozzle region decreased with the increase in ambient density but a reverse trend was observed at downstream because the spray atomization was terminated faster at high ambient densities. Particularly large droplets were observed near the spray head due to the coalescence of liquid droplets accelerated by the vortex flow. The increase in ambient density brought this large droplet regime closer to the nozzle with the further increase in the droplet sizes.